Explaining the decoupling of freight traffic growth and economic growth - Kveiborg, Ole; Fosgerau, Mogens (Proceedings from the Annual Transport Conference at Aalborg University, 2004)
In recent years we have in many European countries seen a decoupling of the growth in freight traffic (vehicle km) from economic growth. A similar decoupling has not been seen in freight transport (tons km). In this paper we analyse the historical development in freight transport and freight traffic using a decomposition methods described in Fosgerau and Kveiborg (2004). The growth in freight traffic can be attributed to various factors with economic growth as an important factor, but there are also important explanations caused by the development in vehicle size, average load and average length of trips as well as the logistical element of freight transport described by the handling factor, which links produced amounts in tons to tons conveyed. Through the analysis we point out the impact these factors have on overall development in freight traffic and freight transport. We further demonstrate that overall freight traffic growth is a consequence of often opposite pointing growth effects in the underlying factors. We find that the primary reason for the decoupling of freight traffic growth and economic growth can be attributed to growth in vehicle sizes, increasing average load and less empty running with the vehicles.